2003
DOI: 10.1016/s0029-7844(03)00341-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting term and preterm delivery with transabdominal uterine electromyography

Abstract: Transabdominal uterine electromyography predicts delivery within 24 hours at term and within 4 days preterm. This methodology offers many advantages and benefits that are not available with present uterine monitoring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
86
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 18 publications
12
86
1
Order By: Relevance
“…However, (Maner, 2003) found that uterine electrical activity occurred within 1Hz and that the maternal heart-rate was always higher than 1Hz. Furthermore, 95% of the patients measured had respiration rates of 0.33 Hz or less.…”
Section: Methodsmentioning
confidence: 92%
“…However, (Maner, 2003) found that uterine electrical activity occurred within 1Hz and that the maternal heart-rate was always higher than 1Hz. Furthermore, 95% of the patients measured had respiration rates of 0.33 Hz or less.…”
Section: Methodsmentioning
confidence: 92%
“…The pre-processing technique used in (Leman H, Marque C, 1999) passed the EHG signal through a Butterworth filter configured to filter 0.8-4 Hz, 0.3-4 Hz, and 0.3-3Hz frequencies. However, (Maner, 2003) found that uterine electrical activity occurred within 1Hz and that the maternal heart-rate was always higher than 1Hz. Furthermore, 95% of the patients measured had respiration rates of 0.33 Hz or less.…”
Section: Methodsmentioning
confidence: 92%
“…Studies have shown that the analysis of EHG can conduct an independent and easier way to monitor labour evolution [12, 13]. Maner et al [14] in their work determined whether delivery can be predicted using EHG. Moslem et al [15] in their work investigated whether pregnancy can be successfully monitored and labour can be accurately predicted using EHG.…”
Section: Introductionmentioning
confidence: 99%